Breaking the silence : human rights violations based on sexual orientation. - Amnesty International United Kingdom (London : Amnesty International United Kingdom, 1997)
Fonds Suzan Daniel (FSD)
Engels
Monografie
Keywords: mensenrechten; seksuele identiteit